Influence of alcohol intake during lactation in the origin of alcohol addiction - Patrícia Bossolani Charlo Sanches; Victor Augusto Pacheco; Amanda Platkitka Maximiano; Marcelo Picinin Bernuci (Rev Rene)
Objective: to analyze the influence of alcohol intake during lactation in alcoholism onset.Methods: descriptive research with intentional convenient sample of 33 people addicted to alcohol and their mothers which assessed the correlation between the consumption of alcohol ingested using the instruments Cut down, Annoyde by criticims, Guilty and Eye-opener, and Tolerance, Annoyed, Cut down and Eye-opener. Results: addicts are men, young, single, with low level of education and income between one and five minimum wages. Among the patients who consider themselves alcoholics, 55.5% had mothers who considered themselves alcoholics and 60.0% of them had consumed alcohol during lactation, but this correlation was not significant. Conclusion: a positive correlation between alcohol consumption by mothers during breastfeeding and addiction of their children in adulthood was not found.